Analysis of Critical Thinking Skills For Students on Biotechnology Materials - S. Syamsurizal; Farah Azizah; Sintia Putri; Fitri Arsih (Tropical Genetics, 2022)
Critical thinking skills can be developed through the learning process. Biotechnology material requires students' critical thinking skills in the learning process. SMAN 1 Payakumbuh has done critical thinking skills in the learning process but it is still not optimal, and data on critical thinking skills are still unknown. This study aims to analyse the level of Critical Thinking Skills of Class XII Students of SMAN 1 Payakumbuh about Biotechnology Materials. This type of research is descriptive research with simple random sampling technique. The instrument used in this study was a test of students' critical thinking skills, and a validity test questionnaire. The data analysis technique used is quantitative descriptive analysis and qualitative descriptive analysis. Based on the results of the research that has been carried out, the data obtained that the results of the critical thinking skills of class XII students of SMAN 1 Payakumbuh were analysed per indicator. The conclusion of this study is the level of critical thinking skills of each indicator of class XII students of SMAN 1 Payakumbuh at low qualification qualifications with an average of 50.59%.